1994
DOI: 10.1002/aoc.590080209
|View full text |Cite
|
Sign up to set email alerts
|

The association between selenium and humic substances in forested ecosystems—laboratory evidence

Abstract: In the soils and aquatic systems of coniferous forests, selenium is usually associated with humic substances. To clarify further some of the mechanisms involved, labelled and unlabelled selenite were added to two forest floors and to a brownwater lake. Sequential extraction procedures and chromatographic methods were used to evaluate the resulting association between selenium and humic substances. It was observed that the forest floors fixed most of the added selenite by means of microbial reductive incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 20 publications
5
49
0
Order By: Relevance
“…This association is possibly due to either selenium-metal-organic matter complexation, such as Se-Fe(III)-organic matter complexes, or due to biotic formation via microbial reduction of Se and further incorporation into soil organic matter structure (Gustafsson and Johnsson, 1994;Fernández-Martínez and Charlet, 2009). Most studies indicated that the association relies more on biotic formation than on abiotic complexation (Fernández-Martínez and Charlet, 2009).…”
Section: Soil Types Peat Sand Marine Clay Fluvial Clay Loessmentioning
confidence: 99%
See 4 more Smart Citations
“…This association is possibly due to either selenium-metal-organic matter complexation, such as Se-Fe(III)-organic matter complexes, or due to biotic formation via microbial reduction of Se and further incorporation into soil organic matter structure (Gustafsson and Johnsson, 1994;Fernández-Martínez and Charlet, 2009). Most studies indicated that the association relies more on biotic formation than on abiotic complexation (Fernández-Martínez and Charlet, 2009).…”
Section: Soil Types Peat Sand Marine Clay Fluvial Clay Loessmentioning
confidence: 99%
“…Methodology to determine Se speciation in soils has been explored intensively either using various single step soil extractions (Yamada and Hattori, 1989;Abrams et al, 1990a;Kang et al, 1991b;Gustafsson and Johnsson, 1992;Johnsson, 1992;Gustafsson and Johnsson, 1994;Alam et al, 2000;Keskinen et al, 2009;Tolu et al, 2011;Qin et al, 2012;Stroud et al, 2012) or sequential soil extractions (Chao General introduction and Sanzolone, 1989;Tokunaga et al, 1991;MacLeod et al, 1998;Mao and Xing, 1999;Wang and Chen, 2003;Hagarová et al, 2005). In general, these soil extractions represent different Se pools or Se fractions present in soils that are removed by the corresponding extractants, such as soluble Se, exchangeable Se, Se adsorbed to metal-(hydr)oxides or carbonates, and Se bound to organic matter or humic compounds, instead of specific Se species (Tokunaga et al, 1991).…”
Section: Selenium Speciation In Soilsmentioning
confidence: 99%
See 3 more Smart Citations